Study of operating modes in the process of selection and tailoring of package materials in the preparation of men’s outerwear - Xodjayeva, Kamola; Rasulova, Mastura (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract: Objective. In this article, taking into account the natural and climatic conditions of Uzbekistan, the formation and study of a package of materials for men's outerwear that meets functional and operational requirements was carried out. Methods. Under laboratory conditions, the types of insulating layers used for outerwear, their properties and physical and mechanical parameters of packaging samples were studied. At the same time, the characteristics of mineral wool, which is one of the natural raw materials as an insulation layer produced in Uzbekistan (suitable and cheap for the climatic conditions of uzbekistan), were studied and compared and compared with the performance of the existing insulation layer. packaging samples. Results. Based on a comparative comprehensive analysis of various insulating materials, as well as requirements for working conditions and overalls for protection from the cold, it can be concluded that mineral wool showed the best results in terms of heat retention. A model sample of men's outerwear was developed based on the use of mineral wool as an insulating layer of men's outerwear and the formation of a clothing package. Conclusion. In the process of sewing a bag of clothes, the operating modes of the sewing machine were studied and the best option for the type of needle and needle pressure was recommended.